The Loyalty of the Customers of the Hostels of the City of Riobamba- Ecuador - Arguello Erazo, Stalin Efrén (2017)
In recent years there has been a growing increase in hotel services, having a competitiveness among them, making it essential to implement strategies to attract and retain customers. The strategies applied to keep customers called loyalty arise to respond to this constant need to improve revenue and reduce outflows. Loyalty in the hotel sector is measured by different factors such as cognitive, affective, conative and action